The teaching work in higher education business groups and the stock market on the stock exchange: A study of the conflicts - Thayse Ancila Maria de Melo Gomes; Roberto Leher; Hellen Balbinotti Costa (Arizona State University, 2020)
The present article identifies and summarizes the conflicts involving teaching work in the public education groups, with stocks market on the stock exchange [B]³, that work in Brazilian higher education: Ânima, Estácio, Kroton and Ser Educacional. Using a methodology for the analysis of social conflicts, this research focuses on existing conflicts in these teaching organizations that involve teachers and students. The survey was based on reports that mentioned the occurrence of conflicts in the organizations studied (2009-2018). In total, there were 102 reports reporting 56 conflicts. From this survey, it was possible to verify that teachers working in these groups deal with pedagogical reforms that favor online disciplines, overcrowding in classrooms, and dismissals. For the characterization of the educational groups the research used information from the Censo da Educação Superior, the electronic portal of the stock exchange, the websites of selected business groups, magazines and specialized newspapers. This investigation concludes that the analysis of these conflicts allows greater understanding of the changes coming from financial control of educational organizations.